Cretomania : Modern Desires for the Minoan Past - Farnoux, Alexandre (British School at Athens - Modern Greek and Byzantine Studies, 2017)
Cover -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- Preface and acknowledgements -- Introduction: Cretomania - desiring the Minoan past in the present -- PART I CRETOMANIA AND THE BUILT ENVIRONMENT - CONSCIOUS, UNCONSCIOUS AND COINCIDENTAL ALLUSIONS IN MODERN ARCHITECTURE AND RECONSTRUCTIONS -- 1 Orthochronicity and its (dis)contents: Cretomania and Frank Lloyd Wright -- 2 Identity and freedom: some observations on Minoan and contemporary Greek architecture -- 3 The artistic reception of Minoan Crete in the period of Art Deco: the reconstruction of the palace at Knossos . . . and why Arthur Evans was right -- PART II CRETOMANIA IN THE VISUAL AND PERFORMING ARTS, AND OTHER CULTURAL PRACTICES -- 4 The Minoan woman as the Oriental woman: Mariano Fortuny's Knossos scarves and Ruth St. Denis -- 5 From Russia with love: Minoan Crete and the Russian Silver Age -- 6 Lord of the dance: Ted Shawn's Gnossienne and its Minoan context -- 7 The ocean liner Aramis: a voyage to the land of Minos and Art Deco -- 8 Cretomania and neo-paganism: the Great Mother Goddess and gay male identity in the Minoan Brotherhood -- PART III CRETOMANIA IN LITERATURE - DIALOGUES WITH RHEA GALANAKI -- 9 Minoans and the postmodern critique of national history: two novels by Rhea Galanaki -- 10 Rhea Galanaki's The Century of Labyrinths: a dialogue between literature and archaeology that starts with Minos Kalokairinos -- 11 Growing up next door to Knossos and 'the other Ariadne' -- Afterword -- List of contributors and abstracts -- Index -- Plates.